An empirical investigation of consumers’ green purchase intentions: the roles of perceived green value and utilities of consumption - Yuan, Ruizhi (2016)
The shift towards a green consumerism has been globally evident since the 1980s. Government, business and individuals have become increasingly aware of the concept of “green” to reduce the environmental footprint of goods and services. These movements have also spawned a dramatic increase in the number of researches into consumer’s green behaviours. Major advances in green consumption literature in the past years have been made with a focus on the following dimensions: personal beliefs (Kilbourne & Pickett, 2008); environmental knowledge (Chan, 2001); environmental attitudes (do Paco et al., 2013); environmental values (Koller et al., 2011); social influence and government policies (Ozaki, 2011) and a set of environmental barriers (Bray et al., 2011). Many of these prior studies have involved models derived from the field of psychology (Ozaki & Sevastyanova, 2011), sociology (Gadenne et al., 2011), and institutional change (Shove, 2010).